Suppose S(n) represents the sum of squares of first n natural numbers.
Our hypothesis is that S(n) = n (n+1) (2n + 1) / 6.
To prove this hypothesis (and thereby convert into a theorem), let us use principle of mathematical induction.
Base Case
S(1) = 1^2 = 1, Also, 1 * (1+1) * 3 / 6. Therefore, Base Case is satisfied.
Induction Hypothesis
Let us suppose the hypothesis is true for all values of n < m.
Inductive Step [Here, we should P(n | n < m) => P(m).]
Let us evaluate S(m). By definition, S(m) = S(m -1) + m^2.
By induction hypothesis, S(m-1) = (m-1) * (m - 1 + 1) * (2(m-1) +1) / 6. This can be used by us, since induction hypothesis allows us to assume hypothesis is true for all values of n < m, and therefore, specifically that it is true for n = m-1.
Therefore, we have
S(m) = (m - 1) * (m) * (2m - 1) / 6 + m^2. By rearranging terms, we get:
S(m) = m/6 {(m - 1) (2m - 1) + 6m}.
That is,
S(m) = m/6 {2m^2 - 2m - m + 1 + 6m}
S(m) = m/6 {2m^2 + 3m + 1}
S(m) = m/6 (m+1) (2m + 1)
Therefore, the hypothesis is true for m.
Since Induction base is satisfied, and induction step is satisfied, therefore, by PMI, hypothesis is true for all values of n >= 1.
Therefore, we have:
S(n) = n (n+1) (2n + 1) / 6.